Fabrication of liquid antibacterial wound dressing with flexible mechanical properties based on polyvinyl alcohol/xanthan gum - Ying Liu; Xuehong Ren; Yuxia Zheng; Maoli Yin; Mengdi Zuo (Materials & Design, 2025)
Wound dressings play a crucial role in promoting skin wound healing. In this work, a novel type of liquid dressing was developed based on polyvinyl alcohol (PVA) and xanthan gum (XG), to which glycerin was added as the moisturizing ingredient; a highly efficient N-halamine antibacterial agent 1-chloro-2,2,5,5-tetramethyl-4-imidazolidinone (MC) was incorporated with ethanol as the solvent. The sample with 25 wt% of MC/ethanol solution (0.2 wt%) showed excellent film formation ability, flexibility, softness, and transparency. The prepared liquid dressing was characterized using Atomic Force Microscopy and X-ray Diffraction analysis. Inhibition zone test and direct contact method were performed and results showed that PVA/XG-MC film could inactivate 6.12 and 6.04 logs of S.aureus and E.coli in 5 min, respectively. In vitro whole blood clotting index determination, hemolysis and cytotoxicity tests showed that PVA/XG-MC dressing possessed improved blood clotting ability, blood compatibility and biocompatibility. In vivo wound healing tests presented that PVA/XG-MC dressing could significantly promote healing process for both uninfected and S. aureus infected wounds with fewer inflammatory cells, more neovascularization and collagen, and greater granulation tissue area was detected in wounds treated with PVA/XG-MC. The prepared PVA/XG-MC dressings may have potential to be used in clinical skin care.